Pengaruh Pemberian Infused Water Kurma dan Lemon Terhadap Kenaikan Kadar Hemoglobin pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Rawajitu Timur - Shinta Novita; Amalia Indah P (Malahayati Nursing Journal, 2024)
ABSTRACT Anemia in pregnancy is a condition with hemoglobin levels 11gr/dL in the first and third trimesters. According to the Lampung Provincial Health Office, in 2019 the prevalence of anemia increased to 23.2% of 6,230 pregnant women. Giving dates and lemon infused water drinks is rich in iron and contains vitamin C which can help increase hemoglobin levels. This study aims to determine the effect of giving date and lemon infused water on the increase in hemoglobin levels of third-trimester pregnant women in the working area of East Rawajitu Health Center. Using the Quasi Experiment method with a population of 32 people and a research sample of 30 people. The intervention group was given 250 ml of date and lemon infused water every day for 14 days and continued to take Fe tablets at night. The control group only drank Fe tablets at night, then an evaluation was carried out after 14 days using a daily checklist sheet. Univariate and bivariate data analysis. The results showed that the average increase in hemoglobin levels of pregnant women before being given treatment was 10.17 gr/dL and after being given it was 11.56 gr/dL. The control group had an average initial hemoglobin level of 10.13 gr/dL and a final hemoglobin level of 10.50 gr/dL with a difference of 0.55 gr/dL. This study proves that there is an effect of consuming infused water of dates and lemons on increasing hemoglobin levels in third trimester pregnant women with a p-value of 0.00. The conclusion from date and lemon infused water is very useful for increasing hemoglobin levels in third trimester pregnant women by continuing to consume Fe tablets in accordance with government programs, continuing to carry out routine pregnancy checks and consuming more foods containing iron and vitamin C as an effort to prevent anemia. Keywords: Infused Water of Dates and Lemons, Hemoglobin Levels  ABSTRAK Anemia dalam kehamilan adalah kondisi dengan kadar hemoglobin 11gr/dL pada trimester I dan III. Menurut Dinas Kesehatan Provinsi Lampung pada tahun 2019 prevalensi anemia meningkat menjadi 23,2% dari 6.230 ibu hamil. Pemberian minuman infused water kurma dan lemon kaya akan zat besi serta mengandung vitamin C dapat membantu meningkatkan kadar hemoglobin. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian infused water kurma dan lemon terhadap kenaikan kadar hemoglobin ibu hamil trimester III di wilayah kerja Puskesmas Rawajitu Timur. Menggunakan metode Quasi Experiment dengan populasinya sebanyak 32 orang dan sampel penelitian 30 orang. Kelompok intervensi diberikan infused water kurma dan lemon sebanyak 250 ml setiap hari selama 14 hari dan malam hari tetap meminum tablet Fe serta kelompok kontrol hanya meminum tablet Fe di malam hari, lalu dilakukan evaluasi setelah 14 hari menggunakan lembar ceklist harian. Analisa data secara univariat dan bivariat. Hasil penelitian didapatkan rata - rata peningkatan kadar hemoglobin ibu hamil sebelum diberikan perlakuan yaitu 10,17 gr/dL dan sesudah diberikan menjadi 11,56 gr/dL. Kelompok kontrol rata - rata kadar hemoglobin awal yaitu 10,13 gr/dL dan kadar hemoglobin akhir 10,50 gr/dL dengan selisih perbedaan 0,55 gr/dL. Penelitian ini membuktikan ada pengaruh dari mengkonsumsi infused water kurma dan lemon terhadap peningkatan kadar hemoglobin pada ibu hamil trimester III dengan p-value 0,00. Kesimpulan dari infused water kurma dan lemon ini sangat bermanfaat untuk meningkatkan kadar hemoglobin pada ibu hamil trimester III dengan tetap mengkonsumsi tablet Fe sesuai dengan program dari pemerintah, tetap melakukan pemeriksaan kehamilan secara rutin serta lebih banyak mengkonsumsi makanan yang mengandung zat besi dan vitamin C sebagai salah satu upaya pencegahan anemia. Kata Kunci: Infused Water Kurma dan Lemon, Kadar Hemoglobin